Factors that affected University Malaysia Kelantan student choose an airline services to travel: case study Selangor - Siah Ai Nee; Cameras Sakayam; Nurul Amera Norhisham; Nurul Aina Fatin Mohammed Nasir (2016)
This study was based on the study on the factors that affects University Malaysia Kelantan student to choose an airline service to travel, that focus at Selangor. Researchers discussed this topic to understand the factors that considered by students during they choose an airline services to travel since we found that research and study based on students to choose airline is less. Researchers had done the study based on University Malaysia Kelantan students as university students will travel to Selangor for vacation during semester break. The research adopted a convenience sampling. This research collected the data by primary data which using questionnaire distribute for respondents. This research was carried out to know among all the factors which are safety, time and service quality that affects most towards the student decision making process to choose the specific airline services. However, all of the stated factors are equally important on their own ways to decision making process. This research was focusing on factors that affect student's decision making process through quantitative research. By utilizing descriptive analysis and Pearson Correlation Coefficient the relationship between factors and customer choice regarding research question can be proven. This research also used multiple regressions to analyze the value of a variable based on the value of two or more other variables.